Quantitative comparison of luminescence probes for biomedical applications. (9th July 2021) - Krajnik, B; Golacki, L W; Fiedorczyk, E; Bański, M; Noculak, A; Hołodnik, K M; Podhorodecki, A
Abstract: Optical imaging holds great promise for the early-stage detection of diseases. It plays an important role in the process of protecting the patient's health. Most of the organic dyes suffer due to photobleaching, light scattering, short light penetration depth, and autofluorescence of specimen, thus, need to be replaced with alternative nanoprobes emitting light in the optical biological window (700–1350 nm). The group of candidates which can challenged described problems are colloidal quantum dots (e.g. CdSe and PbS) and upconverting nanocrystals (e.g. NaGdF4 :Er, Yb). This paper presents comprehensive and systematic studies of the aforementioned probes, using specially designed tissue phantom, and custom-built wide-field fluorescence microscope. We investigated how the absorption and scattering of light at the water, hemoglobin, and intralipid may affect the intensity of luminescence probes and the quality of optical images. We propose a protocol, that could be easily implemented for investigating other nanoprobes that allow for comparison of their optical performance.